Cybersecurity behaviour of smartphone users in India: an empirical analysis. (2nd January 2020) - Shah, Pintu; Agarwal, Anuja
Abstract : Purpose: For a good number of Indians, their smartphone is their first digital computing device. They have less experience in dealing with the Internet-enabled device and hence less experience in handling security threats like malware as compared to users of other countries who have gone through the learning curve of handling such security threats using other Internet-enabled devices such as laptop and desktop. Because of this, the inexperienced Indian smartphone user may be vulnerable to Internet-related security breaches, as compared to the citizens of developed economies. Hence, it is essential to understand the attitude, behaviour and security practices of smartphone users in India. Limited research is available about the security behaviour of smartphone users in India as the majority of research in this domain is done outside India. Design/methodology/approach: In this empirical study, the researchers identified 28 cybersecurity behaviours and practices through a survey of relevant literature. An online survey of identified cybersecurity behaviours and practices was administered to 300 smartphone users. Frequency analysis of the respondent data was done to understand the adoption of recommended cybersecurity behaviours and practices. Pearson's chi-square with 5% level of significance has been used to test the hypotheses. Post hoc analysis with Bonferroni correction was conducted for statistically significant associations. Findings: Overall, the respondents did not exhibit good cybersecurity behaviour. Respondents have adopted some of the most popular security features of the smartphone such as the use of screen lock. However, respondents have not adopted or are not aware of the technical security controls such as encryption and remote wipe. Statistically significant differences were found between the cybersecurity behaviour and practices and independent variables such as gender, age, mobile operating system (OS) and mother tongue. Respondents reported high level of motivation to protect their device and data, whereas they reported moderate level of threat awareness and the ability to protect to their device and data. Results of the comparative analysis with a similar study in China and the USA are also reported in this study. Research limitations/implications: The main limitations of this study are as follows: the respondents' perceptions about their cybersecurity behaviours and practices were measured as opposed to their actual behaviours and practices and the generalizability of the study is limited because the sample size is small as compared to the total number of smartphone users in India. Practical implications: The findings of this study may be useful for the design of effective cybersecurity prevention and intervention programs for general smartphone users of India. Originality/value: This study provides an insight about cybersecurity behaviour of smartphone users in India. To the knowledge of the researchers, this is the first study to collect such quantitative data of smartphone users in India for a better understanding of the cybersecurity behaviours and practices. This study identified 28 cybersecurity behaviours and practices, which smartphone users should follow to improve cybersecurity.